Age-specific seroprotection after Hepatitis B virus vaccination among Korean American pediatric population in Queens, New York - Esther Min; Jae Min; Roger Kim (Taylor & Francis Group, 2022)
Hepatitis B Virus (HBV) infection is a major health issue among Asian Americans. The prevalence of chronic Hepatitis B infection in New York City is estimated to be 2.7% compared with .3% in the overall United States. The efficacy and long-term immunity of HBV vaccination in the Korean American pediatric population in Queens, NY, are not well explored. This study aimed to 1) determine the age-specific prevalence of anti-HBs seropositivity in the Korean American pediatric population and 2) assess biologic/demographic factors influencing immunologic response to HBV vaccine. We performed a retrospective chart review of patients registered to a pediatric health clinic located in Queens, NY, from October 2014 to October 2020. Out of 604 medical records of patients aged ≤18 years who received a completed series of HBV vaccines during infancy, we analyzed 91 medical records where HBV serology test (HBsAg and anti-HBs) results were available. Three out of 91 subjects were born to HBsAg-positive mothers. Eight out of 91 subjects were born in South Korea. Overall, 54.9% of subjects were anti-HBs-seropositive. The seropositive rate in the 15 to 18-years-old-age group (14.3%) was significantly lower than that in other age groups: < 1 year (100%) (p = .015), 1-4 years (52.6%) (p = .033), 5-9 years (63.3%) (p = .0034), and 10-14 years (64%) (p = .0063). The mean duration since vaccination in seropositive subjects was 96.5 ± 53.9 months, and that in seronegative subjects was 121.7 ± 64.2 months (p < .047). Gender, BMI, and foreign birth were not significant risk factors affecting the nonseroprotective status. The role of routine screening of anti-HB titers and booster vaccination in this endemic community needs to be further explored.